2007
DOI: 10.1111/j.1442-2042.2007.01766.x
|View full text |Cite
|
Sign up to set email alerts
|

Penoscrotal histoplasmosis following bladder carcinoma

Abstract: Abstract:Histoplasmosis is caused by a dimorphic fungus Histoplasma capsulatum. Transmission is via inhalation and lungs are the most commonly affected site. Other sites are involved uncommonly and genitals are rarely involved. The case is reported herein of a man with penoscrotal histoplasmosis following bladder carcinoma that had been treated with intravesical bacille Calmette-Guerin. He presented with multiple ulcers on the penis and scrotum that coalesced , followed by the appearance of cutaneous lesions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…Genital histoplasmosis in India has been first reported by Randhawa et al from epididymal biopsy in 1995 17 . It has also been reported by Chaurasia et al in 2007 in a patient with penoscrotal histoplasmosis following bladder carcinoma 18 . A case of epididymal and prostatic histoplasmosis was reported from Karnataka State of southern India, in a 37-year-old male renal transplant recipient 19 .…”
Section: Methodssupporting
confidence: 66%
“…Genital histoplasmosis in India has been first reported by Randhawa et al from epididymal biopsy in 1995 17 . It has also been reported by Chaurasia et al in 2007 in a patient with penoscrotal histoplasmosis following bladder carcinoma 18 . A case of epididymal and prostatic histoplasmosis was reported from Karnataka State of southern India, in a 37-year-old male renal transplant recipient 19 .…”
Section: Methodssupporting
confidence: 66%
“…Subramanian et al (9) report 18 additional cases diagnosed in India. Review of the literature revealed 51 more cases in India, 3 probable cases, 1 unpublished case mentioned in a review, and 2 cases from personal communications (13–48). Thirteen cases have been diagnosed in the United Kingdom in patients with prior residence on the Indian subcontinent (10), and 1 case was diagnosed in Canada in a patient who had recently traveled to India (49).…”
Section: Discussionmentioning
confidence: 99%
“…However, cutaneous histoplasmosis is uncommon and involvement of the penoscrotal area is extremely rare. 3 The present case highlights the need to consider histoplasmosis in the differential diagnosis of Fournier’s gangrene.…”
mentioning
confidence: 76%